CREATIVE TOURISM SATISFACTION (STUDI KASUS DI KAMPUNG KREATIF DAGO POJOK KOTA BANDUNG) - Vany Octaviany; Ersy Ervina; Dwiesty Dyah Utami (Jurnal Akrab Juara, 2019)
This study aims to determine the gap between the expectations and challenges of tourists who come to Dago Pojok Creative Village in Bandung, so that all stakeholders involved can increase the value of tourism products in Dago Pojok Creative Village in Bandung. The research method in this study uses the Importance-Performance Analysis method. The sample in this study were tourists who visited the Dago Pojok Creative Village in Bandung as many as 100 people. From the research results obtained from the research results obtained from the expectations and assessments submitted for Dago Pojok Creative Village, with an average value of 4.64 expectations while the performance received by tourists with an average value of 3.78. Dago Pojok Bandung City still has not provided an average rating of expectations that is greater than the expectations of tourists towards the Creative Village. However, Quadrant B attributes that have been implemented well by the manager of Dago Pojok Creative Village Bandung City Item 2, namely the design of building murals, Item 3 is the design of the art performance space, Item 6 is a source of information obtained after searching the art. and Item 10, the Athmosphere in Dago Pojok Creative Village in Bandung.